Pendampingan Perhitungan Harga Pokok Produksi Jumputan Berdasarkan Pesanan Pada UMKM Galeri Wong Kito - A.R, Sopiyan; P, Periansya; F, Firmansyah (Nanggroe: Jurnal Pengabdian Cendikia, 2024)
This community service aims to provide assistance. This service program aims to help partners analyze the calculation of the cost of production and calculate depreciation costs for fixed assets and electricity costs to factory overhead costs so that the cost of production reflects the correct price. This is because Partners still use simple and simple calculations. In calculating the cost of production, the Wong Kito Palembang Gallery UMKM Junputan Business has not classified costs correctly. To get a solution, apart from being given knowledge and skills related to financial bookkeeping, partners are also given assistance in calculating the cost of production for orders.